(untitled) (Journal of The Colloquium for Information Systems Security Education, 2026)
Rapid advances in AI, automation, and hyperconnectivity are outpacing human habits, producing pervasive ambiguity. Drawing on John Dewey’s philosophy of habit as growth through disruption and inquiry, this paper reconceptualizes cybersecurity education as cultivating reflective, cyber-attuned habits across society—not only training specialists. Dewey’s account of growth through disruption, inquiry, and reorganization are translated into three educational design moves: (1) embed reflective inquiry within procedural exercises; (2) employ inquiry-based, experiential formats (e.g., capture-the-flag, cyber-defense exercises, cyber-ranges) to practice reasoning under uncertainty; and (3) extend learning to social practices of verification and shared deliberation beyond technical settings. The approach turns error into material for growth and equips learners to act with intelligent adaptability. Rather than proposing a fixed framework, the paper offers a conceptual position grounded in Deweyan philosophy, highlighting design implications that can inform educational practice across varied contexts.